2023
DOI: 10.3390/electronics12183903
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Miners’ Dynamic Equilibrium in Blockchain Networks under DDoS Attacks

Xiao Liu,
Zhao Huang,
Quan Wang
et al.

Abstract: Proof of work (PoW) is one of the most widely used consensus algorithms in blockchain networks. It mainly uses the competition between mining nodes to obtain block rewards. However, this competition for computational power will allow malicious nodes to obtain illegal profits, bringing potential security threats to blockchain systems. A distributed denial of service (DDoS) attack is a major threat to the PoW algorithm. It utilizes multiple nodes in the blockchain network to attack honest miners to obtain illega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We also experimented with the Multichain, IPFS, Bitcoin, and Ethereum blockchain platforms. However, we ultimately opted not to use these platforms [10]. We found that the Command Line (CMD) version of the Multichain application was incompatible with the Linux version, and the Graphical User Interface (GUI) was only available with 64-bit architecture, which consumes more power compared to other blockchain applications.…”
Section: Research Methodology and Test Bed Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…We also experimented with the Multichain, IPFS, Bitcoin, and Ethereum blockchain platforms. However, we ultimately opted not to use these platforms [10]. We found that the Command Line (CMD) version of the Multichain application was incompatible with the Linux version, and the Graphical User Interface (GUI) was only available with 64-bit architecture, which consumes more power compared to other blockchain applications.…”
Section: Research Methodology and Test Bed Developmentmentioning
confidence: 99%
“…Additionally, the Bitcoin platform does not offer private blockchain features for our test network data transmission, which is only available for financial purposes. Finally, IPFS was not suitable for our Local Area IoT test network as IPFS is more suitable for cloud data transactions [10].…”
Section: Research Methodology and Test Bed Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, we elaborate on the research content of Table 3. Huang et al [30] established a profit model of miners' resistance to DDoS attacks by using the dynamic evolutionary game method and solved the optimal mining strategy of miners in different network environments by using the Friedman method. Mirkin et al [31] implemented an Incentive-Based Denial of Service (IBDoS) attack using a blockchain reward mechanism to disrupt the operation of a PoW-based cryptocurrency system using a dynamic game approach.…”
Section: Static Game Methodsmentioning
confidence: 99%